Pengaruh Intensitas Pemeriksaan Pajak dan Penagihan Pajak Terhadap Penerimaan Pajak sebagai Kajian Literatur - Anggara, Tommy (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to examine the effect of tax audit intensity and tax collection on tax revenue in Indonesia through a literature review approach. The method employed is a library research design by analyzing ten scientific articles published between 2015 and 2025. The results indicate that tax audits consistently have a positive and significant effect on tax revenue, as they increase the probability of detection and enhance taxpayer compliance. Meanwhile, tax collection also contributes to state revenue, although its effectiveness tends to vary and remains suboptimal in certain cases. These findings are consistent with Deterrence Theory, which emphasizes the importance of enforcement and sanctions in encouraging tax compliance. Furthermore, this study identifies gaps in the implementation of tax collection, suggesting the need for policy optimization and improvements in tax administration quality. Therefore, an effective combination of tax audits and tax collection is expected to sustainably enhance tax revenue.